Evaluation of long term clinical outcome of cervical carcinoma treated with concurrent chemo radiotherapy using ABS guidelines - Hapuarachchi, T.D (My University, 2009)
A retrospective review was conducted of 44 consecutive patients treated at the National University Hospital, Singapore with concurrent chemotherapy, and following ABS guidelines for radiotherapy for definitive cervical cancer treatment beaten January 2001 and January 2006. The median follow up time was 21 months, 5 year overall survival rate and cause specific survival rate were 72.3 percent and 5 years DFS rate was 74.7 percent, The commonest late toxicity was rectal toxicity. Grade 3 and 4 rectal or urinary toxicities were rare. The commonest site of failure was in distant sited followed by loco-regional sites